Bilingual education as 'glocal' capital: statements of educational outcomes on Vietnamese bilingual schools' websites. Issue 6 (2nd July 2020) - Nguyen, Trang Thi Thuy
ABSTRACT: This article examines Vietnamese bilingual schools' statements of educational outcomes on their websites. Data were gathered from websites of seven schools that were publicly accessible on the Internet. The analysis suggests that the schools purported to provide students with different explicit and implicit outcomes related to language, accreditation, extracurricular experience, qualification and virtue, whereby portraying themselves as providers of linguistic, cultural, social and economic capital that was important for the students' upward mobility. The schools, in responding to the social demands, claimed to include not only the issues of global significance, but also the global – local balance in their education, and purported to provide students with a kind of 'glocal' capital through their bilingual education. The schools' discourse of glocal capital – through which they portrayed their 'ideal self' – however may be merely a business tactic to attract potential clients. Further research hence may focus on parents' and students' voices about schools' educational outcomes to draw a more comprehensive picture of the education market.